KEHAMILAN DI LUAR NIKAH SEBAGAI ALASAN MENDESAK DISPENSASI PERKAWINAN: Married By Accident As Grounds For Urgent Marriage Dispensation - Azizah Sekariani; Khairani Bakri (Reformasi Hukum Trisakti, 2026)
One of the requirements for marriage in Indonesia, based on Article 7 paragraph (1) of Law No.1/1974 in conjunction with Law No.16/2019, stipulates a minimum age limit of 19 years for men and women. If this requirement is not met, the state provides the opportunity to apply for a marriage dispensation to the court on urgent reasons. The problem in this study whether premarital pregnancy can be used as an urgent reasons in applying for a marriage dispensation according to Law No.16/2019 jo. PERMA No.5/2019. This research is a descriptive normative legal study using secondary data analyzed qualitatively and drawing conclusions deductively. The result and conclusion, based on the analysis on Judicial Number 42/Pdt.P/2021/PA.Tas, the judge rejected the request for dispensation due to incomplete administrative requirements without considering the pregnancy condition in depth. In fact, premarital pregnancy should be considered an urgent reason in accordance with Article 53 of the KHI regarding premarital pregnancy and the principle of child welfare as regulated in Law No.4/1979.